2022
DOI: 10.1021/acschemneuro.2c00405
|View full text |Cite
|
Sign up to set email alerts
|

Role of Necroptosis in Central Nervous System Diseases

Abstract: Necroptosis is a type of precisely regulated necrotic cell death activated in caspase-deficient conditions. Multiple factors initiate the necroptotic signaling pathway, including toll-like receptor 3/4, tumor necrosis factor (TNF), dsRNA viruses, and T cell receptors. Presently, TNF-induced necroptosis via the phosphorylation of three key proteins, receptor-interacting protein kinase 1, receptor-interacting protein kinase 3, and mixed lineage kinase domain-like protein, is the best-characterized process. Necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 202 publications
0
2
0
Order By: Relevance
“…It is reported that necroptosis, a new form of regulated cell deaths (RCDs), plays a role in the pathogenesis of ALI/ARDS. ,, Necroptosis, first defined by Yuan group, can be activated in a wide range of human inflammatory-involved diseases. Mechanism of necroptosis has been relatively clear by numerous efforts in the past 2 decades . Various death receptors, such as TNF receptor-1 (TNFR1), CD95 (Fas), interferons (IFNs), and IFN-induced Z-DNA binding protein 1 (ZBP1), could initiate necroptosis pathway. Briefly exemplified by TNFR1, tumor necrosis factor-α (TNF-α) interacts with TNFR1 to form signaling complex I on the membrane .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that necroptosis, a new form of regulated cell deaths (RCDs), plays a role in the pathogenesis of ALI/ARDS. ,, Necroptosis, first defined by Yuan group, can be activated in a wide range of human inflammatory-involved diseases. Mechanism of necroptosis has been relatively clear by numerous efforts in the past 2 decades . Various death receptors, such as TNF receptor-1 (TNFR1), CD95 (Fas), interferons (IFNs), and IFN-induced Z-DNA binding protein 1 (ZBP1), could initiate necroptosis pathway. Briefly exemplified by TNFR1, tumor necrosis factor-α (TNF-α) interacts with TNFR1 to form signaling complex I on the membrane .…”
Section: Introductionmentioning
confidence: 99%
“…One of the key inflammatory mediators under neurodegenerative condition is the soluble tumor necrosis factor (TNF) that primarily acts through binding TNF receptor 1 (TNFR1) and activating downstream signaling, including cell death pathways [7]. There is also growing evidence that TNFR1 signaling is implicated in multiple neurodegenerative conditions [8], including AD [9], Parkinson’s disease [10], and multiple sclerosis [11].…”
Section: Introductionmentioning
confidence: 99%